Surviving an infectious disease outbreak: How does nurse calling influence performance during the COVID‐19 fight? - Zhou, Yan; Asante, Eric Adom; Zhuang, Yiyu; Wang, Jie; Zhu, Yue; Shen, Lihua (Blackwell Publishing Ltd, 2020)
Aim: To assess the performance of frontline nurses, who believed they were living out their calling, during the Coronavirus Disease 2019 (COVID-19) pandemic. Background: Although as a profession nursing generally requires high levels of performance, the disruption arising from an infectious disease outbreak increases the work stress and decreases the performance of frontline nurses. How this situation can be improved has yet to be thoroughly examined. Method: We used a snowball sampling technique to recruit 339 nurses who were originally from outside of Hubei but volunteered to join medical teams going to Hubei to tackle COVID-19. Results: Drawing on the theory of work as a calling, we found that living a calling had a positive effect on frontline nurses’ performance through the clinical and relational care they provided. Perceived supervisor support strengthened these mediated relationships. Conclusion: Our findings indicate that despite the constraints associated with pandemics, frontline nurses who are living a calling are able to provide better clinical and relational care to infected patients, which in turn improves their performance. Implications for Nursing Management: The findings of this study suggest that hospitals can introduce career education interventions to enhance nurses’ ability to discern and live out their calling to improve their performance.